Responses by the brown planthopper, nilaparvata lugens, to conspecific density on resistant and susceptible rice varieties - Horgan, Finbarr G.; Naik, Bhaskar S.; Iswanto, Eko Hari; Almazan, Maria Liberty P.; Ramal, Angelee Fame; Bernal, Carmencita C. (Wiley, 2016)
This study examines the nature of intraspecific interactions among Nilaparvata lugens (Stål) (Hemiptera: Delphacidae) planthoppers feeding on resistant and susceptible rice varieties. Planthopper nymphs produced less honeydew and gained less weight when feeding on rice variety IR62 (resistant) compared to susceptible rice varieties. A series of bioassays was conducted that varied N. lugens nymph densities on IR62 and IR22 (susceptible). Increasing nymph density facilitated feeding by conspecifics; however, intraspecific competition increased mortality of nymphs on IR62 (but rarely on IR22). Furthermore, nymph weights declined with increasing conspecific density on IR22, and the effects were weak on IR62. More female nymphs than males survived on IR62 but this was not affected by density. Nitrogenous fertilizer increased competition among N. lugens on young plants of IR22, but not on IR62. Results indicate that nymphs have a low efficiency in accessing resources when feeding on IR62, even where the plants have received fertilizer. Female‐biased survival and biomass compensation for mortality may promote population recovery after development on the resistant plant and accelerate adaptation to the resistant variety.